THE GEOCHEMISTRY OF VOLCANIC PLUGS INTRUDING SHALES OF THE PINDIGA FORMATION, GONGOLA SUB-BASIN, NORTHERN BENUE TROUGH, NIGERIA: IMPLICATIONS FOR PROVENANCE, WEATHERING, AND TECTONIC SETTING - Auwalu, Dalha; Ahmed, Isah Haruna; Abubakar, Usman; Yusuf, Abubakar; Mboringong, Miranda Nchang; Adeyinka, Olasehinde; Babanya, Ahmad Abubakar; Kamale, Ishaku Hamman (FUDMA Journal of Sciences, 2026)
This study presents a geochemical investigation of volcanic plugs intruding the Cretaceous shales of the Pindiga Formation in the Gongola Sub-Basin, Northern Benue Trough, Nigeria. Eight representative samples comprising basalts (n = 4), shales (n = 3) and sandstone (n = 1) were analyzed for major oxides using wavelength-dispersive X-ray fluorescence (WD-XRF). Analytical accuracy was monitored using certified reference standards and analytical precision is better than ±5% for major oxides. The basaltic plugs plot within the sub-alkaline field on the TAS diagram and display a tholeiitic affinity on the AFM diagram. One basalt sample shows a peraluminous signature (A/CNK > 1), which may reflect assimilation of Al-rich country rocks during magma emplacement. Geochemical proxies suggest that the shales were predominantly derived from mafic igneous sources and are classified as Fe-shales. High Chemical Index of Alteration (CIA = 85.39–95.67) and low Index of Compositional Variability (ICV = 0.31–0.51) indicate intense chemical weathering under humid paleoclimatic conditions. Major-element tectonic discrimination diagrams suggest a tectonic setting consistent with an active continental margin, although interpretations are made cautiously due to the limited dataset and the known limitations of major-element proxies. The results provide new geochemical constraints on the relationship between Cenozoic magmatism and the Cretaceous sedimentary succession of the Gongola Sub-Basin.